Hadron production in e+e- annihilation at sqrt s =29 GeV. - Derrick, M; Fernandez, E; Gan, K; Fries, R; Hyman, L; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; et al. (1987)
Data from the High Resolution Spectrometer at the SLAC storage ring PEP have been used to study the inclusive production of baryons and mesons. Time-of-flight measurements are used to identify the charged hadrons. Neutral hadrons are identified from effective-mass peaks associated with their decay into two charged particles. Cross sections and other inclusive production characteristics are presented for , K, and K0 (K0) mesons, and for the baryons (antibaryons) p (p) and (). The ratio of the inclusive cross section to the point cross section for the K0 and K0 mesons is R(K0,K0)=6.150.130.25, and for and , R()=0.8460.0360.085. The neutral-hadron differential cross sections are compared with the predictions of the Lund string model. © 1987 The American Physical Society.